Circular Futures: Navigating the Built Environment of 2035 - Patrick Moloney; Scott Brookes; Ricardo Weigend Rodriguez (Economia Creativa)
This conceptual exploration employs strategic foresight to envision built environment trajectories through the lens of the circular economy. Using the scenarios method and Dator’s four archetypes (Collapse, Continued Growth, Discipline, Transformation), the manuscript outlines alternative futures and emphasises a preferred “Discipline” scenario aligned with circular principles. It highlights the value of anticipatory thinking in informing infrastructure, policy, and design decisions that promote sustainability and resilience. By embedding circularity into foresight processes, the work offers a structured framework for guiding systemic change in the built environment, encouraging long-term strategic action toward regenerative, low-impact urban futures.